Farmers’ Preference for IARI Wheat Varieties in North Western Plain Zone and Central Zone of India - Anirban Jana,; Nishi Sharma,; M.S. Nain,; Sitaram Bishnoi,; Rajat Kumar Nath, (Indian Journal of Extension Education, 2025)
This research work was conducted to identify preferred traits of Triticum aestivum and Triticum durum wheat among farmers in North-Western Plain Zone (NWPZ) and Central Zone (CZ) of India, respectively. The survey was conducted in 2023, and the method of sampling used for choosing 120 farmers was multi-stage random sampling, of which 60 farmers were from Aligarh, Uttar Pradesh, and 60 farmers were from Dewas, Madhya Pradesh. SPSS was used to perform quantitative conjoint analysis of the preferences for plant height, crop duration, irrigation requirement, pest attack, grain yield, grain size, and straw yield. From observations taken during the interviews, farmers preferred early maturity, species or hybrids with high grain and straw yield, large grain size, high market price, low water usage through irrigation, and disease or pest attack rating. Grain yield and straw yield, grain size, and market rate had a very high influence on preference, while plant height had the least influence. These insights can inform future wheat breeding programs aligned with preferences by farmers to improve food production in the NWPZ and CZ regions. Understand what these preferences are and formulate varieties that will meet the requirements for better food production.